Understanding Consumers’ Privacy Concerns in Online Shopping: Antecedents and Consequences - Zhang, Kexin (2013)
The impressive prevalence of Internet has contributed a lot to the collection and analysis of personal data, thus posting threats to people’s privacy. This research aims at understanding the antecedents and consequences of privacy concerns within online purchase context by an empirical study based on 113 Chinese online users of young or middle age. Consumers’ perceived vulnerability to disclosure, perceived control over the content and ways of disclosure, and previous experience of online shopping were proposed as three antecedents of privacy concerns online. And the impacts of privacy concerns on consumers’ willingness to disclosure under online purchase circumstances as well as the moderating role of trust towards the websites were examined.